Development and optimization of specially designed air ventilation system combined with thermoelectric and composite desiccant unit - Dararat Tongdee; Somchai Maneewan; Surapong Chirarattananon; Chantana Punlek (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This research focused on the enhancement of a conventional air ventilation system by using monitoring control. A specially designed system was developed to optimize the current systems in order to improve the air quality and thermal comfort in buildings. Indoor parameters, such as temperature, humidity, and air pollution (CO2), were monitored and controlled. Researchers accumulated data and implemented performance analysis as a tool for assessing specially designed air ventilation systems. These practices were designed based on a concept that is dedicated outdoor air systems that were comprised of a composite desiccant unit in addition to a thermoelectric module to address tremendous latent and sensible loads of air inlet. The results of the experiment indicated that the 12 V of electrical supply to thermoelectric provided the highest COP of the system, and the temperature and humidity in the comfort zone was approximately 27 ๐C and 55%, respectively, due to this newly developed system. Furthermore, the CO2 levels were lower than 1000 ppm during this research study, which were in accordance with established standards of indoor air quality.